Association between gastroesophageal reflux disease and metabolic syndrome: a bidirectional two-sample Mendelian randomization analysis - Tao He; Xiaoling Geng; Xue Lin; Yufei Li; Zhijun Duan (Archives of Medical Science)
Introduction Methods Results Conclusions